PENGEMBANGAN MODEL ADAPTASI ROY PADA KONSEP DIRI PASIEN DENGAN PEMASANGAN FIKSASI EKSTERNAL DI RSO Prof. Dr. R. SOEHARSO SURAKARTA - Prasetyo, Budi (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2014)
Installation of external fixation is the method of reduction and immobilization, for the handling of fractures. One of the impact of external fixation mounting is the change in self?concept. Self-concept according to Stuart (2005) consists of 5 components. Roy in his theory emphasizes the concept of adaptation in overcoming stressor. The study was conducted to explore the self-concept of the patient with the installation of an external fixation using Roy's adaptation model development. Research using phenomenological qualitative research design. The population was patients who received external fixation installation management (including Ilizarov) undergoing inpatient and outpatient care (control) in the RSO Prof. Dr. R. Soeharso Surakarta. Total sampling technique was used and the participants get 7 people. The experiment was conducted 4 weeks. Instruments using interviews and fields notes that have been tested for validity and reliability. Processing and data analysis using methods of data interpretation (Speziale & Carpenter, 2003) and software NVivo 9.0.204.0. Research carried out by applying the principles of research ethics. Generated 14 themes, which is an indication of mounting external fixation, development theory, significant other theory, self?perception theory, additional traits, coping mechanisms, body image, ideal self, self-esteem, role performance, personal identity, nursing care services, expectations of participants, and the difficulties experienced by participants. Concluded a negative self-concept changes (adaptation ineffective) on all participants. Roy adaptation model development in the assessment of changes in self-concept in the installation of external fixation in the hospital, very appropriately to used.Keywords: Roy adaptation model, self-concept, external fixation